Functional characterization of superoxide dismutase in Candida dubliniensis and effect of decyl methyl carbinol - Goh, Meng Chuan (2012)
Candida dubliniensis is a Candida species that is closely related to Candida albicans. Although they share high similarity in both genotypic and phenotypic characteristics including the capability to undergo mycelia transformation from yeast to hypha/pseudohyphae, C. dubliniensis is found to be less virulent, more susceptible to antifungal drugs and more sensitive to oxidative stress environment when compared to C. albicans. Superoxide dismutase (Sod) is an important enzyme that disproportionates superoxide free radical anions that are generated from oxidative stress. Although C. dubliniensis consists of all the SOD ortholog sequences which have been found in C. albicans, C. dubliniensis is unable to sustain significant growth at temperature higher than 40°C when compared to C. albicans. Apart from that, quorum sensing molecule (QSM) has been found to be proficient in suppressing morphological switching from yeast to hyphal transition in both C. albicans and C. dubliniensis. Decyl methyl carbinol (2-dodecanol), a recently identified QSM molecule that has been tested in C. albicans is found to have suppressed the yeast to hyphal transformation in hyphal-induced condition. 2-dodecanol also found to suppress certain hyphal-specific genes (HSGs). The current study is focused on the morphological changes of C. dubliniensis at different temperatures. The SOD genes in C. dubliniensis also have been sequenced and characterized and the expression profile at 37°C and 42°C are studied in comparison to C. albicans. The genes expression profiles were quantified using relative quantification real time PCR. Two (2)-dodecanol was used to treat both C. dubliniensis and C. albicans. The morphological transition, toxicity effect and growth rate in both C. dubliniensis & albicans were recorded under the effect of 2-dodecanol. C. dubliniensis HSGs expression profiles were recorded after exposing 2-dodecanol to C. dubliniensis under the hyphalinduced condition. A clinical isolate that is isolated from University Malaya Medical Centre was also molecularly characterized in this study. In the results, C. dubliniensis has formed pseudohyphal at 42°C but unable to grow at temperatures higher than 42°C. The SOD sequences from C. dubliniensis were posted with 85-95% similarity when aligned with the orthologs sequences from C. albicans. Despite sharing a certain level of similarities in the SOD sequences, a total of 5 SOD genes in C. dubliniensis were upregulated in 42°C when compared to C. albicans that with only 2 SOD genes being upregulated. This study discovers that, the over-expression of Sod in C. dubliniensis could lead to the accumulations of high concentration of hydrogen peroxide and cause C. dubliniensis unable to survive in high temperatures. 2-dodecanol, however, showed with the effect to preserve both C. albicans and C. dubliniensis in round shaped yeast form. Nevertheless, C. dubliniensis is significantly more sensitive to high concentration of 2- dodecanol in terms of fungicidal and fungistatic effect. HSGs expression in C. dubliniensis under the exposure to 2-dodecanol also vary from what has been seen in C. albicans and constant expression of cdHSP90 can be the main factor that kept C. dubliniensis in the yeast form. Interestingly, in this study, we also discovered that the clinical isolate that resembled both C. dubliniensis & C. albicans are the potential interspecies or intra-species between these two closely related species.